2022
DOI: 10.3389/fmed.2021.756398
|View full text |Cite
|
Sign up to set email alerts
|

Varying Dose of Atropine in Slowing Myopia Progression in Children Over Different Follow-Up Periods by Meta-Analysis

Abstract: Purpose: To evaluate the efficacy and safety of atropine for slowing myopia progression and to investigate whether the treatment effect remains constant with continuing treatment.Method: Studies were retrieved from MEDLINE, EMBASE, and the Cochrane Library from their inception to May 2021, and the language was limited to English. Randomized controlled trials (RCTs) and cohort studies involving atropine in at least one intervention and placebo/non-atropine treatment in another as the control were included and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
3
10
1
2
Order By: Relevance
“…In our case, we found that atropine 0.01% had similar effect during the first and second year of treatment in terms of mean SE progression (− 0.42 ± 0.41 D and − 0.45 ± 0.39 D, respectively). However, these results differ from the results of the ATOM 2 (phase 2) and LAMP 2 Asian studies that found better efficacy with atropine 0.01% during the second year 12 , 35 , 36 . While some studies have found a decrease in treatment efficacy 37 , 38 , other have also found similar efficacy over the 2-years of treatment 21 , 33 .…”
Section: Discussioncontrasting
confidence: 99%
“…In our case, we found that atropine 0.01% had similar effect during the first and second year of treatment in terms of mean SE progression (− 0.42 ± 0.41 D and − 0.45 ± 0.39 D, respectively). However, these results differ from the results of the ATOM 2 (phase 2) and LAMP 2 Asian studies that found better efficacy with atropine 0.01% during the second year 12 , 35 , 36 . While some studies have found a decrease in treatment efficacy 37 , 38 , other have also found similar efficacy over the 2-years of treatment 21 , 33 .…”
Section: Discussioncontrasting
confidence: 99%
“…In this meta-analysis, we combined the results from 27 RCTs and 17 cohort studies, and confirmed that there was significantly less myopia progression (WMD = 0.45 D/year; high dose: 0.73 D/year; moderate dose: 0.65 D/year, low dose: 0.35 D/year) and slower axial elongation (WMD = −0.15 mm/year; high dose: −0.26 mm/year; moderate dose: −0.37 mm/year, low dose: −0.11 mm/year) in the atropine group than in the control group. These results are similar to two previously published meta-analyses ( Gong et al, 2017 ; Gan et al, 2021 ). Moreover, we observed linear and nonlinear dose−response correlations, suggesting that as the concentration increases, the ESs of atropine on retarding refraction and axial length progression increases.…”
Section: Discussionsupporting
confidence: 93%
“…Secondary outcomes included risk of rapid (>1.0 D/year)/slow (<0.5 D/year) myopia progression ( Gan et al, 2021 ; Ha et al, 2022 ), progression in different treatment duration (D/year, mm/year), rebound effect (D/year, mm/year), progression in 3 years (D, mm), accommodation change (D), photopic pupil diameter change (mm), best-corrected visual acuity change (BCVA, logMAR/year), astigmatism change (D/year), anterior chamber depth change (ACD, mm/year), corneal curvature change (D/year), intraocular pressure change (IOP, mmHg/year), lens thickness change (LT, mm/year) and incidence of photophobia, blurred near vision and allergic reactions. Among them, the first four outcomes evaluated the efficacy of atropine, and the other secondary outcomes evaluated the safety of atropine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We started with 0.02, 0.03, and 0.05% atropine in low-risk, moderate-risk, and high-risk groups, respectively. It is known that atropine has a significant dose-dependent effect on refractive change, axial elongation, and adverse effects (15). We choose 0.02% atropine as a starting dose instead of 0.01% in low-risk group based upon below reasons: (1) 0.02% atropine had a better effect on myopia progression than 0.01% atropine, but 0.02% and 0.01% atropine showed similar effects on pupil diameter and accommodative amplitude (16).…”
Section: Discussionmentioning
confidence: 99%